Commuting Mobility as Risk Factor for Dengue Hemorrhagic Fever in Sleman Regency, Yogyakarta, Indonesia - Kesetyaningsih, Tri Wulandari; Amir, Siti Fajrini; Desty, Yeni Rahma (Universitas Ahmad Dahlan, 2020)
Background:In Indonesia, there has been a change in the age group of dengue hemorrhagic fever (DHF) patient population from children to adults since 1998. It raises the suspicion that an infection occurs not only in residential area but also from other places as a result of human mobility. Research on the role of people mobility as a risk factor for dengue incidence yielded different results. This study aims to reveal the relationship between human mobility and the incidence of dengue. Method: This is a case-control study that involved 276 respondents; 138 were sufferers (case group) while the other 138 respondents were non-sufferers (control group). The sample size was determined by using purposive sampling. Patient’s data and their addresses were obtained from Sleman Regency Health Office while the control group was patient’s neighbors. The people mobility data were obtained by conducting questionnaires that were divided into three categories, namely low, moderate, and high for commuting mobility and two categories, namely traveling outside and inside province for circular mobility. Chi-square analysis was used to determine whether mobility was a risk factor for DHF. Results:The result showed that commuting mobility was correlated with the DHF incidence (p=0.001) where the high mobility of 3.169 times raised the risk of DHF incidence (OR 3.169; 95% CI: 1.690-5.944) more than the low mobility. However, the DHF incidence was not correlated with moderate mobility (p=0,821). Furthermore, traveling outside the Yogyakarta Province reduced the risk by 6.175 times than non-traveling activity (p=0.000; OR 6.175; 95% CI: 2.759-13.822). Conclusion: The commuting mobility outside the village is a risk factor of DHF. Meanwhile, traveling outside Yogyakarta Province did not cause any risk for DHF and it instead tended to reduce the risk.